Xylitol production from waste xylose mother liquor containing miscellaneous sugars and inhibitors: one-pot biotransformation by Candida tropicalis and recombinant Bacillus subtilis. Issue 1 (December 2016) - Wang, Hengwei; Li, Lijuan; Zhang, Lebin; An, Jin; Cheng, Hairong; Deng, Zixin
Abstract Background The process of industrial xylitol production is a massive source of organic pollutants, such as waste xylose mother liquor (WXML), a viscous reddish-brown liquid. Currently, WXML is difficult to reuse due to its miscellaneous low-cost sugars, high content of inhibitors and complex composition. WXML, as an organic pollutant of hemicellulosic hydrolysates, accumulates and has become an issue of industrial concern in China. Previous studies have focused only on the catalysis of xylose in the hydrolysates into xylitol using one strain, without considering the removal of other miscellaneous sugars, thus creating an obstacle to subsequent large-scale purification. In the present study, we aimed to develop a simple one-pot biotransformation to produce high-purity xylitol from WXML to improve its economic value. Results In the present study, we developed a procedure to produce xylitol from WXML, which combines detoxification, biotransformation and removal of by-product sugars (purification) in one bioreactor using two complementary strains, Candida tropicalis X828 andBacillus subtilis Bs12. At the first stage of micro-aerobic biotransformation, the yeast cells were allowed to grow and metabolized glucose and the inhibitors furfural and hydroxymethyl furfural (HMF), and converted xylose into xylitol. At the second stage of aerobic biotransformation, B. subtilis Bs12 was activated and depleted the by-product sugars. The one-pot process was successfully scaled up from shake flasks to 5, 150 L and 30 m3 bioreactors. Approximately 95 g/L of pure xylitol could be obtained from the medium containing 400 g/L of WXML at a yield of 0.75 g/g xylose consumed, and the by-product sugars glucose, l -arabinose and galactose were depleted simultaneously. Conclusions Our results demonstrate that the one-pot procedure is a viable option for the industrial application of WXML to produce value-added chemicals. The integration of complementary strains in the biotransformation of hemicellulosic hydrolysates is efficient under optimized conditions. Moreover, our study of one-pot biotransformation also provides useful information on the combination of biotechnological processes for the biotransformation of other compounds.